Interaction Effects and Population-attributable Risks for Smoking and Alcohol on Laryngeal Cancer and Its Subsites - Ramroth, H.; Dietz, A.; Becher, H. (Methods of Information in Medicine, 2004)
Objectives: To assess the joint effect of smoking and alcohol consumption on laryngeal risk on tumor subsites.Methods: Population-based case-control study in South-West Germany with 257 histologically confirmed cases (236 males, 21 females), age 37 to 80 years, and 769 population controls (702 males, 67 females), 1:3 frequency matched by age and sex.Results: Half of the tumors (50.6%) were glottic or subglottic, 17.5% were supraglottic. Due to advanced stage, the subsite of 31.9% of the tumors could not be determined clearly. There is a strong increase in risk with increasing tobacco consumption with an odds ratio (OR) of 59.8 (95% confidence interval (CI) 21.3-167.3) for heavy smoking (>80 packyears (py)), all cases combined. In comparison to current smokers, cancer risk is reduced for ex-smoking (>2 years) OR=0.36, 95% CI 0.24-0.53. The risks were higher for supraglottic than for glottic and sub-glottic tumors. The effect of alcohol is not as strong. A significantly increased odds ratio of 2.0, 95% CI (1.0-3.9) results for 75-100 g ethanol/day only for glottic and subglottic tumors. The OR rises from 2.2, 95% CI (1.1-4.3) for 100-150 g ethanol/day to 4.3, 95% CI (1.4-13.2) for more than 150 g ethanol/day (all models adjusted for education). The joint effect of smoking and alcohol results appears sub-multiplicative but super-additive. Almost 90% of the tumors can be attributed to both factors.Conclusion: Contrary to earlier investigations we observed a sub-multiplicative effect of smoking and alcohol. The risk for persons with both high alcohol and tobacco consumption is extremely high which indicates the importance of intervention.
Keywords: Case-control studies; laryngeal cancer; tobacco and alcohol consumption; interaction; population attributable risk